Psychometric Properties of the Self-as-Context Scale with a University Counseling Center Sample - Robert D. Zettle; Grace A. Lyons; Jonathan M. Larson; Christopher Leonard (Behavioral Sciences, 2025)
The model upon which acceptance and commitment therapy is based posits that its outcomes are mediated by increased psychological flexibility as a core process. Of the six subprocesses contributing to psychological flexibility, self-as-context has been investigated the least due to a lack of adequate assessment. An evaluation of the psychometric properties of at least one such measure—the Self-as-Context Scale (SACS)—has been primarily limited to nonclinical populations. To address this omission, we administered the SACS to students (N = 132) seeking psychological services from their university counseling center. A confirmatory factor analysis failed to find an adequate fit for a previously reported two-dimensional model of the SACS, suggesting that only total scores may be appropriate in research and practice involving clinical samples. All 10 items satisfactorily loaded on a single factor to produce reliable total scaled scores, which were, as expected, significantly lower for our participants than those from a general college student sample. Even lower scores were obtained for outpatients of a psychology training clinic compared to our sample, which provided additional support for the known-groups validity of the SACS. The limitations of the findings and implications for further investigations of the measure’s psychometric and functional properties are discussed.